GENERAL DATA PROTECTION LAW: PRIVACY IN THE VIRTUAL WORLD - Moreira da Veiga Pessoa, Bruno (Revista Gênero e Interdisciplinaridade, 2023)
Amidst the technological advances brought with the 21st century, the way in which people practice their routine activities has been transformed, all of which have been adapting to the practicality brought about by the digital revolution. In this sense, this article analyzed the ways in which information transactions between users occur and how this data is stored and processed, in view of the General Data Protection Law, which seeks to guarantee greater security in the virtual world so that this environment can become more secure.